2019
DOI: 10.3390/en12234434
|View full text |Cite
|
Sign up to set email alerts
|

New Models Used to Determine the Dioxins Total Amount and Toxicity (TEQ) in Atmospheric Emissions from Thermal Processes

Abstract: In order to reduce the calculation effort during the simulation of the emission of polychlorinated dibenzo-p-dioxins and furans (PCDD/F) during municipal solid waste incineration, minimizing the number of simulated components is mandatory. For this purpose, two new multilinear regression models capable of determining the dioxins total amount and toxicity of an atmospheric emission have been adjusted based on previously published ones. The new source of data used (almost 200 PCDD/F analyses) provides a wider ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Previous work at the Universitat Ramon Llull (URL) (Palmer et al, 2019(Palmer et al, , 2018 showed a dependence on the dioxin and furan emissions from thermal decomposition of different products. This work established three linear regression models that were able to estimate properly the total amount and toxicity of a sample considering only the amount of 1,2,3,6,7,8-HxCDD, OCDF and 2,3,7,8-TCDF in the sample.…”
Section: Correlation Between Congener Emissions In Thermal Decomposit...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work at the Universitat Ramon Llull (URL) (Palmer et al, 2019(Palmer et al, , 2018 showed a dependence on the dioxin and furan emissions from thermal decomposition of different products. This work established three linear regression models that were able to estimate properly the total amount and toxicity of a sample considering only the amount of 1,2,3,6,7,8-HxCDD, OCDF and 2,3,7,8-TCDF in the sample.…”
Section: Correlation Between Congener Emissions In Thermal Decomposit...mentioning
confidence: 99%
“…This kinetic study pretends to be simple in order to be used in a future simulation process, where the operational parameters will be selected for simulating total PCDD/F emissions. In order to simplify the kinetics, a correlation between the formation of the PCDD/F congeners previously published will also be taken into consideration (Palmer et al, 2019(Palmer et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) are classified as dioxins [7][8][9][10]. Each PCDD/DFs can include chlorine atoms up to eight in different places on the molecule [11]. These characteristics result in different types of molecules, such as congeners.…”
Section: Introductionmentioning
confidence: 99%